Do restoration techniques and types of weed control influence the composition of edaphic entomofauna? - Providello, Alexandra; Fujihara, Ricardo T.; Penha, Alessandra S.; Rodrigues, Josiane (Entomological Communications, 2022)
Agroforestry systems (AFS) are generally referred to as systems where perennial plants are associated with annual or perennial crops, spanning from relatively simple agroforestry systems characterized by only two associated species to very complex ones, close to natural systems. However, there are few studies on edaphic entomofauna in newly implanted restoration systems. We investigated the composition of edaphic entomofauna in areas managed under different restoration techniques (agroforestry system or mixed-planting) and types of weed control (chemical or mowing). In each treatment, we performed collections with pitfall traps in July and December 2017. A total of 11,727 specimens distributed in 11 orders and 45 families were collected. Most of the individuals collected were Collembola (53.86%) and Hymenoptera: Formicidae (31.50%). No significant interaction was observed between restoration techniques and types of weed control combined. However, for abundance, both restoration techniques and types of weed control were individually significant, with chemical control showing a higher abundance in relation to mowing, and agroforestry concerning mixed-planting. There was no significant difference in richness in any of the variables studied. We conclude that the agroforestry system and the chemical control can be viable for edaphic entomofauna, although future research is necessary to evaluate the dynamic of edaphic entomofauna during the development of agroforestry systems.